Mitigating the thermal runaway of lithium-Ion batteries in a cell-to-cell configuration - Nadya Binte Abdul Malek (Nanyang Technological University, 2024)
This report evaluates the characteristics and effectiveness of various gas phase flame retardant (FR) additives in mitigating thermal runaway of Lithium-ion pouch cell batteries (LIB) that has undergone TR within a cell-to-cell configuration. The additives that were tested in this report were, aluminium trihydrate (ATH), magnesium hydroxide (MDH), zinc carbonate (ZnCO3), melamine and urea. From this report, it had been noted that FRs that possesses a high enthalpy of decomposition or sublimination were able to effectively lower the maximum temperature rise rate faced by the neighbouring cell (Max Rate). In addition, it was also found that a thicker sample had played a role in lowering the maximum temperature faced by adjacent cell (Tmax) as the thicker barrier was able to reduce the heat transfer between the medium. Additives with lower onset temperature of decomposition had also been observed to lower Tmax due to them having earlier activation to release out the gaseous products such as ammonia, H2O and CO2 during its decomposition reaction. Additionally, additives that are able to be consumed the most within 10s which aids in more gaseous products released during decomposition is seen to have the most minimal effect in lowering maximum temperature of neighbour cell.